Pannexin1: insight into inflammatory conditions and its potential involvement in multiple organ dysfunction syndrome - Chen, Xiangyu; Yuan, Siyi; Mi, Liangyu; Long, Yun; He, Huaiwu (Frontiers in Immunology, 2023)
Sepsis represents a global health concern, and patients with severe sepsis are at risk of experiencing MODS (multiple organ dysfunction syndrome), which is associated with elevated mortality rates and a poorer prognosis. The development of sepsis involves hyperactive inflammation, immune disorder, and disrupted microcirculation. It is crucial to identify targets within these processes to develop therapeutic interventions. One such potential target is Panx1 (pannexin-1), a widely expressed transmembrane protein that facilitates the passage of molecules smaller than 1 KDa, such as ATP. Accumulating evidence has implicated the involvement of Panx1 in sepsis-associated MODS. It attracts immune cells via the purinergic signaling pathway, mediates immune responses via the Panx1-IL-33 axis, promotes immune cell apoptosis, regulates blood flow by modulating VSMCs' and vascular endothelial cells' tension, and disrupts microcirculation by elevating endothelial permeability and promoting microthrombosis. At the level of organs, Panx1 contributes to inflammatory injury in multiple organs. Panx1 primarily exacerbates injury and hinders recovery, making it a potential target for sepsis-induced MODS. While no drugs have been developed explicitly against Panx1, some compounds that inhibit Panx1 hemichannels have been used extensively in experiments. However, given that Panx1's role may vary during different phases of sepsis, more investigations are required before interventions against Panx1 can be applied in clinical. Overall, Panx1 may be a promising target for sepsisinduced MODS. Nevertheless, further research is needed to understand its complex role in different stages of sepsis fully and to develop suitable pharmaceutical interventions for clinical use.